Two-Stage Black-Start Optimization for Power Systems with Multi-Energy Microgrid as a Black-Start Unit - ZHU Yongqing, CHEN Changming, LI Qingsheng, LI Zhen, ZHANG Zhaofeng, LIN Zhenzhi (Shanghai Jiaotong Daxue xuebao)
To reduce the losses caused by major power outages in power systems, a two-stage optimization method for black start of power systems is proposed using a multi-energy microgrid (MEMG) as a black-start source. First, the load-side integrated demand response and the operation characteristics of the electric, thermal, and gas physical energy storage devices in the MEMG are modeled as generalized energy storage. Next, a two-stage optimization model for black start of power systems using the multi-energy microgrid as a black-start source is proposed, with the first stage being the optimization sub-model for non-black-start source restoration path and the second stage being the black-start strategy optimization sub-model considering the power system and the MEMG. Then, a Dijkstra’s algorithm-based solution method for the first stage sub-model and a mixed integer quadratic programming-based solution method for the second stage sub-model are respectively proposed. Finally, a case study of a real regional power system in China is conducted to verify the effectiveness and advantages of the proposed black start optimization method.